Communicable Disease Surveillance and Response in Uganda - Cummings, Matthew (Consilience, 2009)
While outbreaks of communicable diseases have long presented an ongoing challenge in the developing world, within recent years the frequency of such outbreaks has risen sharply. Accordingly, it is clear that strong epidemiological surveillance and response is needed to improve the health of disadvantaged populations in developing nations such as Uganda. Such populations face the greatest threat from communicable diseases and are more likely to fall victim to illness due to their poverty. In Uganda, the implementation of Village Health Teams (VHTs) has laid the groundwork for establishing community-based surveillance and response systems that can provide early notification of outbreaks and prevent the unnecessary suffering that accompanies unrecognized epidemics. Local response programs can also help to identify opportunities for the implementation of sustainable preventive measures and health education activities that will be able to improve the overall welfare of those living in settings of poverty.